The merchant of Venice - Shakespeare, William 1564-1616; Crowther, John (John C.) (New York : SparkNotes, 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Donated by Nimet Kaplan.
Keywords: Shakespeare, William, -- 1564-1616; Jews -- Italy -- Drama; Moneylenders -- Drama; Venice (Italy) -- Drama